The stability of Fe(III)-As(V) co-precipitate in the presence of ascorbic acid: Effect of pH and Fe/As molar ratio. (March 2019) - Yuan, Zidan; Zhang, Guoqing; Lin, Jinru; Zeng, Xiangfeng; Ma, Xu; Wang, Xin; Wang, Shaofeng; Jia, Yongfeng
Abstract: The potential hazards of Fe(III)-As(V) co-precipitate under reducing conditions are incompletely known. This work investigated the effect of Fe(III) reduction by ascorbic acid (AH2 ) on the stability of Fe(III)-As(V) co-precipitate at different pHs and Fe/As molar ratios. The results showed that As (14–98.9%) and Fe (27.9–99.3%) were significantly released into solution by 79.9–97.5% Fe(III) reduction of the co-precipitate (Fe/As molar ratios of 3 and 5) at pH 5–9. More As release was observed with the increase of pH (6–9) or decrease in Fe/As molar ratio (from 5 to 3). This could be attributed by oxalate, the final product of AH2 decomposition, which strongly competed with As(V) for Fe(II) at higher pH or lower Fe/As molar ratio, inhibiting parasymplesite accumulation and then causing more As mobilization. The stability of Fe(III)-As(V) co-precipitate with AH2 upon Fe(III) reduction was lower than that in oxic environment. Compared with produced Fe(II, III) (hydr)oxides in the presence of hydroquinone (QH2 ), humboldtine was formed during the long-term reactions of Fe(III)-As(V) co-precipitate with AH2 . The findings of this study implied that parasymplesite and humboldtine as secondary solid products were environmental relevant and mainly responsible for As(V) and Fe(II) immobilization. Highlights: Fe(III)-As(V) co-precipitate in ascorbic acid solutions is unstable at pH 5−9. More As release occurs upon Fe reduction at higher pH or lower Fe/As molar ratio. Oxalate is the final product of ascorbic acid oxidation under Fe-reducing condition. Oxalate competes with arsenate for Fe(II) inhibiting parasymplesite accumulation. Parasymplesite and humboldtine are main secondary solids for As and Fe fixation.